2012
DOI: 10.1038/onc.2012.432
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-34 suppresses breast cancer invasion and metastasis by directly targeting Fra-1

Abstract: MicroRNAs have key roles in tumor metastasis. Here, we describe the regulation and function of miR-34a and miR-34c (miR-34a/c) in breast cancer metastasis. Expression analysis verified that miR-34a/c expression is significantly decreased in metastatic breast cancer cells and human primary breast tumors with lymph node metastases. Overexpression of miR-34a/c could inhibit breast cancer cell migration and invasion in vitro and distal pulmonary metastasis in vivo. Further studies revealed that Fos-related antigen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
179
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(187 citation statements)
references
References 58 publications
5
179
0
3
Order By: Relevance
“…Therefore, it is possible that upregulated PPARG and downregulated JUND may exert opposite effects on osteosarcoma metastasis via competitively regulating the expression of SAT1. In addition, upregulation of the FOSL1 oncogene is involved in breast cancer migration and invasion (46). FOXA2 may function as a suppressor of lung cancer metastasis by inhibiting TGF-β-induced epithelial to mesenchymal transition (47).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is possible that upregulated PPARG and downregulated JUND may exert opposite effects on osteosarcoma metastasis via competitively regulating the expression of SAT1. In addition, upregulation of the FOSL1 oncogene is involved in breast cancer migration and invasion (46). FOXA2 may function as a suppressor of lung cancer metastasis by inhibiting TGF-β-induced epithelial to mesenchymal transition (47).…”
Section: Discussionmentioning
confidence: 99%
“…In breast cancer, miR34c is related to self-renewal and epithelialmesenchymal transition, and miR34a/c regulates breast cancer migration and invasion (12,26). Interestingly, miR34a directly targets CD44 and suppresses tumor development and metastasis in prostate cancer stem cells (20).…”
Section: Discussionmentioning
confidence: 99%
“…Recent work described that miR-34 suppresses invasion and metastasis of breast cancer by directly targeting Fra-1 (Yang et al, 2012); other reports have shown that p53/miRNA-34 axis regulates snail-dependent epithelialmesenchymal transition in tumorigenesis (Kim et al, 2011). Ectopic miR-34 expression was shown to induce apoptosis, cell-cycle arrest, and senescence (Hermeking, 2010).…”
mentioning
confidence: 99%
“…In triple-negative breast cancer, which is characterized mainly by ERa, PgR, and HER2 absence, miR-34b, but not miR-34a or miR-34c was reported to be negative correlated with diseasefree survival and an overall survival (Svoboda et al, 2012). A microarray conducted in breast cancer has shown that miR34a was significantly downregulated in DCIS and IDC compared with benign tissue (Yang et al, 2012). However, the role of miR-34a in breast cancer still needs to be further elucidated.…”
mentioning
confidence: 99%